ANALISIS PERILAKU KONSUMSI PESERTA DIDIK KELAS XII IPS SMA NEGERI 1 SINGOSARI KABUPATEN MALANG - Shelia Faradila Kusuma; Prih Hardinto (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2019)
Every human being has different consumption behaviors with each other. So that in the motivation and consumption strategies carried out by students also vary, there are students who think rationally and irrationally. This study aims to analyze the consumption behavior of students of class XII IPS in SMA Negeri 1 Singosari. This study uses a qualitative method with a phenomenological approach and for the collection of data sources using snowball sampling technique. Data collection techniques in this study used observation, interviews, and documentation. From the results of the study showed that there were some students in class XII IPS SMA Negeri 1 Singosari in the motivation to consume rationally and irrationally. In addition, there are some students who plan in their consumption strategy.